MATE Transporter-Dependent Export of Hydroxycinnamic Acid Amides. Issue 2 (7th January 2016) - Dobritzsch, Melanie; Lübken, Tilo; Eschen-Lippold, Lennart; Gorzolka, Karin; Blum, Elke; Matern, Andreas; Marillonnet, Sylvestre; Böttcher, Christoph; Dräger, Birgit; Rosahl, Sabine
Abstract : A MATE transporter is required and sufficient for export of hydroxycinnamic acid amides, which act as antimicrobial compounds on the plant surface. Abstract: The ability of Arabidopsis thaliana to successfully prevent colonization by Phytophthora infestans, the causal agent of late blight disease of potato ( Solanum tuberosum ), depends on multilayered defense responses. To address the role of surface-localized secondary metabolites for entry control, droplets of a P. infestans zoospore suspension, incubated on Arabidopsis leaves, were subjected to untargeted metabolite profiling. The hydroxycinnamic acid amide coumaroylagmatine was among the metabolites secreted into the inoculum. In vitro assays revealed an inhibitory activity of coumaroylagmatine on P. infestans spore germination. Mutant analyses suggested a requirement of the p -coumaroyl-CoA:agmatine N 4- p -coumaroyl transferase ACT for the biosynthesis and of the MATE transporter DTX18 for the extracellular accumulation of coumaroylagmatine. The host plant potato is not able to efficiently secrete coumaroylagmatine. This inability is overcome in transgenic potato plants expressing the two Arabidopsis genes ACT and DTX18 . These plants secrete agmatine and putrescine conjugates to high levels, indicating that DTX18 is a hydroxycinnamic acid amide transporter with a distinct specificity. The export of hydroxycinnamic acid amides correlates with a decreased ability of P. infestans spores to germinate, suggesting a contribution of secreted antimicrobial compounds to pathogen defense at the leaf surface.